Systemic Inflammatory Response Syndrome on Admission and Clinical Outcomes After Intracerebral Hemorrhage - Liu L; Wang A; Wang D; Guo J; Zhang X; Zhao X; Wang W (Dove Medical Press, 2023)
Lijun Liu,1,2 Anxin Wang,1,2 Dandan Wang,1,2 Jiahuan Guo,1,2 Xiaoli Zhang,2 Xingquan Zhao,1- 3,* Wenjuan Wang1,2,* 1Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People's Republic of China; 2China National Clinical Research Center for Neurological Diseases, Beijing, People's Republic of China; 3Research Unit of Artificial Intelligence in Cerebrovascular Disease, Chinese Academy of Medical Sciences, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xingquan Zhao; Wenjuan Wang, Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, 119 West Road, South4th Ring, Fengtai District, Beijing, 100070, People's Republic of China, Tel +86-010-59978330 ; Tel +86-010-59978891, Fax +86-010-67013383, Email zxq@vip.163.com; tong_ttyy@163.comBackground: Since studies on systemic inflammatory response syndrome (SIRS) in patients with acute intracerebral hemorrhage (ICH) are insufficient. This study investigated the associations between SIRS on admission and clinical outcomes after acute ICH.Patients and Methods: The study included 1159 patients with acute spontaneous ICH from January 2014 to September 2016. In accordance with standard criteria, SIRS was defined as two or more of the following: (1) body temperature > 38°C or < 36°C, (2) respiratory rate > 20 per minute, (3) heart rate > 90 per minute, and (4) white blood cell count > 12,000/μL or < 4000/μL. The clinical outcomes of interest were death and major disability (defined as a modified Rankin Scale of 6 and 3- 5), combined and separate at 1 month, 3 months and 1 year follow-up.Results: SIRS was observed in 13.5% (157/1159) of patients and independently increased the risk of death at 1 month, 3 months, or 1 year: hazard ratio (HR) 2.532 (95% confidence interval [CI] 1.487- 4.311), HR 2.436 (95% CI 1.499- 3.958), HR 2.030 (95% CI 1.343- 3.068), respectively (P< 0.05 for all). The relationship between SIRS and ICH mortality was more pronounced in older patients or patients with larger hematoma volumes. Patients with in-hospital infections were at greater risk of major disability. The risk was enhanced when SIRS was incorporated.Conclusion: The presence of SIRS at the time of admission was associated with mortality in patients with acute ICH, particularly in older patients and those with large hematomas. SIRS may exacerbate the disability caused by in-hospital infections in patients with ICH.Keywords: systemic inflammatory response syndrome, intracerebral hemorrhage, in-hospital infections, death, disability